SUPERVISION, COMPENSATION, LEADERSHIP AND WORK ENVIRONMENT ON TEACHER WORK DISCIPLINE AT SMPN 1 KUNDURAN BLORA - Widianti, Rizki; Kusasih, Ida Ayu Kade Rachmawati (Universitas Ibn Khaldun Bogor, 2023)
This study aims to determine the effect of supervision, compensation, leadership and work environment on the work discipline of teachers at SMPN 1 Kunduran Blora. Determination of the sample using the saturated sample method, as many as 53 existing populations are all respondents. The data source used is primary data. Methods of data collection using questionnaires and methods of data analysis using data instrument tests, classical assumption tests, and hypothesis testing including multiple linear regression, t test and test the coefficient of determination. The results show that supervision and leadership have a significant effect on work discipline, while compensation and work environment have no significant effect on work discipline